[8+3]‐Cycloaddition Reactions of Heptafulvenes or Azaheptafulvenes with α‐Halohydroxamates. Issue 7 (2nd June 2022) - Xie, Lei; Hu, Lina; Wu, Ping; Zhao, Yunxu; Li, Guiling; Cui, Jichun; Gao, Zhenzhen; Wu, Lingang; Nie, Shaozhen
Abstract: The base‐mediated higher‐order [8+3]‐cycloaddition reactions of heptafulvenes or azaheptafulvenes with α‐halohydroxamates have been achieved under mild and metal‐free conditions. These reactions do not only provide a direct route for the synthesis of highly functionalized cycloheptatriene‐fused piperidinones and piperazinones in moderate to excellent yields, but they also enrich the chemistry of heptafulvenes and azaheptafulvenes. Furthermore, gram‐scale reactions and further derivatizations demonstrated the synthetic potential of these cycloaddition reactions. Abstract : Base‐mediated higher‐order [8+3]‐cycloaddition reactions of heptafulvenes or azaheptafulvenes with α‐halohydroxamates were developed. This strategy produced a variety of cycloheptatriene‐fused piperidinone and piperazinone derivatives in moderate to excellent yields under mild conditions.